Successes and Opportunities for Private Land Conservation In The Flint Hills - Mike Beam (Symphony in the Flint Hills, 2016)
Within the past fifteen years the private landowner community has taken actions to permanently conserve more than 100,000 acres of native grasslands in the Kansas Flint Hills.
Keywords: Flint Hills; conservation; organizations; easements; fish and wildlife; USDA-NRCS; landowners; funding; ALL SPACES SEEM WIDER WITHOUT YOU; Katie Twiss; FIELD